A Review on Kadara and its Multi Modal Treatment Approach with specific reference to Agnikarma (International Journal of Ayurveda and Pharma Research, 2022)
Mankind suffers from a lot of conditions which, on the outlook seem very trivial in comparison to the actual suffering arising out of the condition. Kadara is one such condition, which comes under the umbrella of Kshudra rogas. It is a condition with a simple pathology but causing intense suffering to the patient. Kadara can be correlated to Helomas or foot corns. Foot corns have a simple etiopatholgy but most often, difficult to attain a complete cure. Various treatment modalities available presently for the management of corn include the use of salicylic acid paints, cryosurgery, surgical removal of corn, etc. Recurrence is a common issue in almost all the said modalities. Agnikarma is the classical line of treatment mentioned for Kadara. The present article is a review of the available research works in Ayurveda, taken up in the management of Kadara. Majority of the works available have taken Agnikarma (thermal cauterisation) using various Upakaranas (materials) for treatment, with few other works having other modalities like Lepana (paste application), Chedana (excision) & Kshara karma (application of alkali).